Scaled-up nutrition education on pulse-cereal complementary food practice in Ethiopia: a cluster-randomized trial - Getenesh Berhanu Teshome; Susan J. Whiting; Timothy J. Green; Demmelash Mulualem; Carol J. Henry (BMC Public Health, 2020)
Abstract Background Improving children’s weight status through nutrition education (NE) for mothers about using pulses in complementary feeding has been demonstrated in pilot studies, but no effect on stunting was reported. The aim of the study was to assess the impact of a 9-month pulse-nutrition education program on improving mothers’ knowledge, attitude, and practices (KAP) towards pulses, as well as its effect on children’s diet diversity, and nutritional status. The NE was delivered by Health Extension Workers (HEWs). Methods A cluster randomized study was employed for the community-based interventional study. Twelve randomly selected villages in Sidama Zone, Southern Ethiopia were included in the study. A total of 772 mother-child pairs involved in the study; where 386 mother-child pairs in the intervention group received additional messages about pulse-cereal complementary food, and 386 pairs (the control) received only routine health education for 9 months. A survey on mothers’ KAP and anthropometric measurements of the children were taken at baseline, midpoint, and end point. ANOVA and descriptive statistics were used to analyzed data. Results At baseline and end point, maternal KAP and the dietary diversity score of the children (mean age at end point 18.8 ± 2.9 mo) were assessed. Intervention mothers’ KAP improved (p < 0.001) at midpoint and end point compared to that of the control group, as did frequency of pulse consumption and Dietary Diversity Score (DDS) among children. At 9 months, the prevalence of stunting, wasting, and underweight was significantly reduced in the intervention group compared to the control group (p = 0.001). Conclusions NE delivered by HEWs improved KAP of mothers regarding pulse consumption and dietary diversity of children led to improved nutritional status of the children. Training HEWs on the use of pulses for complementary food may be an effective way to improve the health of children in Ethiopian communities. Trial registration Clinicaltrials.gov # NCT02638571 . Date of registration: 12/18/2015. Prospectively registered.